Sistem Informasi Notifikasi Jadwal Sidang Pada Kantor DPRD Provinsi Sumatera Selatan Berbasis Android - Rohman, Azzam Fadhlur; Yulianingsih, Evi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The South Sumatra Regional People's Representative Council is a regional people's representative institution that is domiciled as an element of regional government administration in the province of South Sumatra. Currently, the process of hearing schedule information at the South Sumatra provincial DPRD office still uses conventional methods such as direct submission of the unit that provides requests for hearings or internal activities, after that the requests will be processed and invitations to session meetings are then distributed. Therefore, it can be overcome by proposing a system, namely the firebase push notification feature or firebase cloud messaging. Firebase cloud messaging is a form of service provided on Google to send a message or notification to customers through a browser or smartphone. The purpose of this study is to build a hearing schedule notification information system in the South Sumatra Provincial DPRD to make it easier for DPRD members to find out information about the trial and get notification of the session schedule on the members' cellphones. This app is designed and built by leveraging Firebase Cloud Messaging by narrating push notifications. This system is expected to be able to manage notifications every time there is a new news update regarding the time and agenda of the trial, as well as provide convenience to members of the DPRD to find out information about the trial.